Trauma, Resonances, and Transformations: Gaming as Heuristic Mode for Doing History - Camarda, Sandra (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2024)
This paper examines the potential of video games as a heuristic tool for engaging with history, particularly in the context of traumatic events and contested narratives. Traditionally, video games have been dismissed as trivial entertainment, unsuitable for addressing complex historical topics. However, new paradigms challenge such perceptions by exploring how ludonarratives – stories shaped by game mechanics –can facilitate transformative learning. By shifting players from passive spectators to active participants, games offer immersive experiences that can encourage critical engagement with historical events. The emotional impact of these experiences, supported by empirical studies, has the potential to promote empathy, understanding, and social change. Building on theories of resonance and transformative learning, this contribution advocates for a re-evaluation of video games’ role in historical education, emphasising their ability to provide meaningful, multi-perspective experiences that deepen our understanding of the past and its relevance to contemporary issues.